In search of some type-specimens of Rhamphus [Clairville], 1798 (Coleoptera: Curculionidae) - Caldara, Roberto; Toševski, Ivo; Mendel, Howard; Germann, Christoph (Zootaxa, 2022)
During morphological and molecular studies of species of Rhamphus from southern and western Europe, the authors realized that some specimens currently identified as R. pulicarius (Herbst, 1795) and R. oxyacanthae (Marsham, 1802), two widely distributed species in Europe, belonged to different closely related taxa. Therefore, it was necessary to examine type specimens of these and other species considered synonymous or confused with them. It was possible to designate lectotypes for Rhamphus subaeneus Illiger, 1808 and Rhamphus kiesenwetteri Tournier, 1873. However, it was necessary to designate neotypes for: Curculio pulicarius Herbst, 1795, Curculio oxyacanthae Marsham, 1802 and Rhamphus flavicornis [Clairville], 1798. These three neotypes were sequenced for mtCOI and the sequences are now accessible online. Moreover, in accordance with Article 23.9 and the Principle of Priority of the Code, because of confirmed synonymy between R. oxyacanthae and R. flavicornis, the former name is officially proposed as nomen protectum and the latter as nomen oblitum. Detailed information regarding historical entomological collections in the Museum für Naturkunde der Humboldt-Universität of Berlin and the Clairville collection in the Naturhistorisches Museum of Basel, relating to our search for relevant type specimens, is provided.